TEACHERS’ PERCEPTION, COMPETENCE, AND SCHOOL SUPPORT IN GASING MATHEMATICS IMPLEMENTATION IN KAIMANA: A MIXED-METHODS STUDY - Randa, Trigarcia Maleachi; Palungan, Chrisaria; Menufandu, Dahlia Gladiola Rurina; Warami, Hugo; Sawaki, Yusuf Willem; Marwa, Jonni (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
This study aims to examine the key factors influencing the implementation of GASING mathematics, particularly teachers’ perception, attitude, competence, and school support, in a rural educational context. The study addresses the limited integration of these variables within a single analytical framework, especially in remote areas such as Kaimana. A mixed-methods approach was employed involving 14 teachers who have experience in implementing the GASING method. Quantitative data were collected using structured questionnaires and analyzed using descriptive statistics and Spearman correlation, while qualitative data were obtained through open-ended responses and analyzed using thematic analysis. The results indicate that all variables are categorized as high to very high, reflecting positive responses toward the GASING method. Correlation analysis shows that teacher competence has the strongest relationship with implementation (r = 0.62), followed by school support (r = 0.52), perception (r = 0.43), and attitude (r = 0.35). These findings highlight the central role of teacher competence in ensuring effective implementation. Qualitative findings further reveal that despite positive perceptions and attitudes, teachers still encounter challenges related to limited practical skills and inconsistent institutional support. This study offers a novel contribution by integrating multiple teacher-related and institutional factors within a mixed-methods framework in a remote context. The findings imply that strengthening teacher competence through continuous professional development, supported by consistent school policies and resources, is essential for optimizing the implementation of innovative mathematics learning approaches such as GASING.